Comparison Of Streaming Performance Using Htlm5 And Flash Player Version 23 - Chystia Aji Putra; Henni Endah Wahanani (Proceeding International Conference on Information Technology and Business, 2017)
Sending information through streaming video is better than text or voice. One type of streaming multimedia is video on demand (vod) which is a multimedia service with streaming process. Streaming video on vod requires wide bandwidth for maximum transmitted data rates. Some say comparing html5 vs flash is like comparing apples and oranges. Html came up with their newest specification called html5 a few years ago. Html5 natively supports on demand and live video streaming sources. Adobe flash, on the other hand, has been the only way to let rich audio and video content run on the web for more than a decade. This research will compare between html5 and flash player. This research will simulating file package transfering scenario which is file size 144p, 240p, 360p, 480p, 720p. Simulation is using mikrotik as a bandwidth management on network. In this research, performance will compared to quality of service (qos) using wireshark. Simulation is done with 100 mb file packet delivery scenario. Results of research will get the performance value of streaming video using html5 and flash player. Analysis includes time span, troughtput, delay, using wireshark. The comparison will be obtained differences in vod performance between html5 and flash player. Keywords : Streaming Performance, HTML 5, and Flash Player.